2020
DOI: 10.1103/physrevb.101.140402
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating magnetism in the topological semimetal EuCd2As2

Abstract: Magnetic Weyl semimetals are expected to have extraordinary physical properties such as a chiral anomaly and large anomalous Hall effects that may be useful for future, potential, spintronics applications. 1,2 However, in most known host materials, multiple pairs of Weyl points prevent a clear manifestation of the intrinsic topological effects. Our recent density functional theory (DFT) calculations study suggest that EuCd 2 As 2 can host Dirac fermions in an antiferromagnetically (AFM) ordered state or a sing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 52 publications
12
49
0
Order By: Relevance
“…We show one magnetic unit cell in Figure 2a where the order is FM within the Eu layers but with alternating direction (AFM) between the layers. This A‐type AFM order has been previously reported in crystals of EuCd 2 As 2 and EuCd 2 Sb 2 , [ 23–27 ] and is consistent with the magnetic susceptibility data in Figure 2b that shows a FM order when H ∥ ab , but an AFM order when H ∥ c . The finite residual χ c ( T ) near zero temperature indicates a small out‐of‐plane spin canting superposed on the A‐type AFM order.…”
Section: Figuresupporting
confidence: 91%
See 2 more Smart Citations
“…We show one magnetic unit cell in Figure 2a where the order is FM within the Eu layers but with alternating direction (AFM) between the layers. This A‐type AFM order has been previously reported in crystals of EuCd 2 As 2 and EuCd 2 Sb 2 , [ 23–27 ] and is consistent with the magnetic susceptibility data in Figure 2b that shows a FM order when H ∥ ab , but an AFM order when H ∥ c . The finite residual χ c ( T ) near zero temperature indicates a small out‐of‐plane spin canting superposed on the A‐type AFM order.…”
Section: Figuresupporting
confidence: 91%
“…Epitaxial techniques can be used to fabricate thin films and heterostructures from this layered compound for AFM spin torque and spin valve devices. [ 17,18 ] It is possible to even change the magnetic state of the material by altering the flux growth condition, as recently reported for EuCd 2 As 2 , [ 25 ] and to replace both Eu and Cd with other rare‐earths and transition metals. [ 34 ] Future efforts in chemical doping, electrical biasing, and mechanical straining will enable tuning of the magnetic fluctuations, hence controlling the temperature/field regime of CMR in EuCd 2 P 2 and its derivatives.…”
Section: Figurementioning
confidence: 96%
See 1 more Smart Citation
“…Recent studies of rare-earth-based metallic systems have revealed novel electronic states arising from a complex interplay of magnetism and electron-band topology [1][2][3][4][5][6][7]. EuMg 2 Bi 2 is one such system that undergoes antiferromagnetic (AFM) ordering below a Néel temperature T N ≈ 6.7 K [8][9][10] and is also reported to host multiple Dirac points located at different energies with respect to the Fermi energy [10].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated recently that the antiferromagnet EuCd 2 As 2 with T N ∼ 9.5 K would be an ideal candidate for the study of the interplay between magnetism and topology, as it exhibits various topological states in both the antiferromagnetic (AFM) and paramagnetic (PM) phases [23][24][25][26][27][28]. In the AFM phase, depending on the direction of the Eu magnetic moments, various nontrivial topological ground states have been predicted, such as magnetic topological Dirac semimetal, or axion insulator, AFM topological crystalline insulator, and higher order topological insulator [27].…”
mentioning
confidence: 99%